Design and development of an omni-directional rover for exploration on undulating terrain - Loh, Wuh Ken (2008)
This report describes the development of a new 6-wheel Omni-Directional Rover (ODR). The primary objective of the work was to develop locomo-tion and wheel mechanism for a rover that can navigate smoothly and omni-directionally on undulating terrain.